Out of site, out of mind: Changes in feather moss phyllosphere microbiota in mine offsite boreal landscapes - Yin, Xiangbo; Martineau, Christine; Samad, Abdul; Fenton, Nicole J. (Frontiers in Microbiology, 2023)
Plant-microbe interactions, including associations between feather mosses from boreal forests and their phyllosphere microbiota, contribute to biodiversity and ecological services in forest biomes. Increases in mining for mineral requirements are potential threats to biodiversity. However, knowledge of impacts of mining on biodiversity in mine offsite landscapes is still poor, especially for microbiomes. We sampled Pleurozium schreberi (Brid.) Mitt. in control sites and within 1-km radial landscapes (away from the edge of each mine site) containing four ecosystem types of the Canadian boreal forest (i.e., coniferous, deciduous, mixed forests and open canopy peatlands) in six mines at different stages of the mine lifecycle. Offsite effects of mines on the phyllosphere microbiota were detected using microbial DNA recovered from the phyllosphere of P. schreberi. Mining stage and ecosystem type both affected alpha and beta diversity as well as the relative abundance of some taxa, generally without interactions between the two factors. Individual microbial taxa were more affected by offsite effects than community-level diversity. The strongest effects occurred within 0.2 km from operating mines. These results indicate that mine sites are structuring microbial communities of the feather moss phyllosphere in boreal landscapes, and that these effects are driven by mining stage and ecosystem type. The results also imply that predicted shifts from coniferous to deciduous dominance in boreal forest under global changes would not modify the impact of mines on the phyllosphere microbiota in offsite landscapes. Further studies are needed to assess how these offsite effects on the phyllosphere diversity and community structure affect the functioning of boreal ecosystems and to develop appropriate mitigation strategies.